Expanding Cultural and Natural Heritage Through Archaeology: An Application of Cultural Keystone Places (CKP) in the Medieval Mediterranean - Forste, Kathleen M.; Pérez-Juez, Amalia; Smith, Alexander J. (Ethnobiology Letters, 2025)
In this article we apply the Cultural Keystone Place (CKP) framework to the island of Menorca, Balearic Islands, Spain, to explore the importance of archaeology in enhancing connections to and valuation of natural and cultural landscapes. Through a brief overview of recent investments made on the island in the environment, agricultural and food heritage, as well as cultural heritage, we discuss the implications of the narrative created by what is and is not claimed or designated as heritage. We are writing from the position of archaeologists working on the island and argue that archaeological investigation of the often-overlooked medieval Islamic era on the island is key to understanding more fully the historical ecology and historical narrative of the island. Following the tenets of CKP, we argue that archaeological visibility can ensure the enduring cultural importance of a place, demonstrating not just its importance to people in the past, but also preserving it for the present and future.